A cidade desejada e sublimada por Jorge Amado: os lugares imaginados em Bahia de Todos-os- Santos: guia de ruas e mistérios de Salvador - Ricardo Araújo Barberena (Estudos de Literatura Brasileira Contemporânea)
The book Bahia de Todos-os-santos: guia de ruas e mistérios de Salvador (Bahia of all-saints: a guide to the streets and mysteries of Salvador), by Jorge Amado (published in 1944), portrays an easygoing and provincial capital of Bahia. The population, which was less than 300 thousand people, moved about in the different celebrations of life. Due to profound urban transformations, the book underwent alterations in the different versions published through the years. However, the underlying structure and the spirit of the book have remained: the production of an encyclopedia of what it means to be/being “baiano” – sceneries, stories, old streets, new avenues, traditions, parties, poverty, joy, churches, candomblé, orishas, and other characters. In its pages, the book presents a real and magical image of a territory permeated by ordinary mysteries. The book has maintained its essence throughout the different editions. Even if the city has changed physically, it remains unchanged in terms of its poetic prose and in the production of a sublime descriptivism of a “black Rome.”